2011
DOI: 10.1016/j.jaapos.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in parents of children with intermittent exotropia

Abstract: Purpose-To assess the health-related quality of life (HRQOL) of parents of children with intermittent exotropia using the newly developed condition-specific Parent Intermittent Exotropia Questionnaire (Parent IXTQ) and the generic PedsQL Family Impact Module (PedsQL FIM) and to compare the performance of both instruments.Methods-One parent was recruited for each of 59 children with intermittent exotropia (age range, 3 to 16; median, 7 years) and for each of 29 visually normal children (age range, 5 to 13; medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 12 publications
2
31
0
3
Order By: Relevance
“…Because, in the present study, we aimed to primarily assess the association between HRQOL and strabismus surgery we included only patients with HRQOL data using the previously described intermittent exotropia HRQOL questionnaire (IXTQ). 68 From mid-2008, we aimed to administer the IXTQ to all children with intermittent XT, minimizing selection bias. IXTQ data were collected as part of a research protocol and were not directly reviewed by the care provider, nevertheless we assumed that any concerns were also expressed to the care provider and that the IXTQ would simply provide a standardized measure of these concerns.…”
Section: Methodsmentioning
confidence: 99%
“…Because, in the present study, we aimed to primarily assess the association between HRQOL and strabismus surgery we included only patients with HRQOL data using the previously described intermittent exotropia HRQOL questionnaire (IXTQ). 68 From mid-2008, we aimed to administer the IXTQ to all children with intermittent XT, minimizing selection bias. IXTQ data were collected as part of a research protocol and were not directly reviewed by the care provider, nevertheless we assumed that any concerns were also expressed to the care provider and that the IXTQ would simply provide a standardized measure of these concerns.…”
Section: Methodsmentioning
confidence: 99%
“…In order to formally measure HRQOL in this population, we previously developed and validated the Intermittent Exotropia Questionnaire (IXTQ), a patient-derived HRQOL instrument for children with intermittent exotropia (XT). (Hatt et al., 2010a, Hatt et al, 2010b, Yamada et al, 2011a, Yamada et al, 2011b) In our previous initial study, Child IXTQ and Proxy IXTQ scores were found to be lower (worse HRQOL) in children with intermittent XT than in normal controls, (Hatt et al, 2010a) nevertheless, responses to individual questionnaire items have not been studied. The purpose of the present study was to assess responses to individual items on Child and Proxy IXTQ on a larger cohort of patients than used in the original validation studies in order to evaluate the impact of specific HRQOL concerns in children with intermittent XT.…”
Section: Introductionmentioning
confidence: 93%
“…1,3,10 We have created conversion tools using Excel spreadsheets (Microsoft Inc) to easily convert raw IXTQ responses to Rasch-scaled responses and have made them available online (http://pedig.jaeb.org/). In addition to logit values, the lookup tool converts each Rasch person measure from a logit value to a 0 to 100 value (0 indicating worst HRQOL and 100 indicating best HRQOL) through a linear transformation of the person scores.…”
Section: Discussionmentioning
confidence: 99%